ANÁLISE DE COMPONENTES PRINCIPAIS PARA O COMPORTAMENTO MORFOLÓGICO E AGRONÔMICO DE GENÓTIPOS DE ALGODOEIRO NO MUNICÍPIO DE UBERABA – MG - RODRIGUES, Josiane; HENRIQUE, Francisco Humberto; PIEDADE, Sônia Maria De Stefano; LACA-BUENDÍA, Julio Pedro (Brazilian Journal of Biometrics, 2020)
It was applied multivariate technique of principal component analysis in order to characterize five cultivars and a new genotype of cotton lines (Gossypium hirsutum r. latifolium Hutch) with respect to morphological and agronomic variables in Uberaba city (MG). The experimental design was the randomized block design with six treatments and four replications, and the genotypes Delta Opal (Delta and Pine), Delta Penta (Delta and Pine), BRS-Cedro (EMBRAPA), IAC-25 (IAC), EPAMIG Precocious I (EPAMIG) and the progenies IAC-06/191 (IAC) were analyzed. The variables evaluated were: height of the first productive branch, height of the plant, diameter of stem at harvest, final stand, total weight of seeds, weight of 100 seeds, weight of a boll, fiber percentage, fiber index and productivity. The principal component analysis allowed the joint visualization of the evaluated variables, being those related to mechanized harvesting and to productivity the ones that were most responsible for the total variability of the data. The BRS-Cedro strain demonstrated high productivity and positive aspects for the mechanical harvesting, which makes it stand out in relation to each one of the other strains. The progeny IAC-06/191 showed that it will favor the good performance of the harvesters, although it did not present high productivity.